Güncel Metasezgisel Optimizasyon Algoritmalarinin Performans Karşilaştirilmasi - Eröz, Eyüp; Tanyildizi, Erkan (Institute of Electrical and Electronics Engineers Inc., 2019)
ÖZETIn this study, the performance of current metasheuristic optimization algorithms are compared. Seven different optimization algorithms were used when comparing performance, inspired by nature and different branches of science. 23 unrestricted benchmarking functions and 2 constrained engineering problems were used to compare the performance. According to the result of the test, the mathematically based Golden Sine Algorithm (GoldSA) and Sinus Cosine Algorithm (SCA) are faster and perform better than other algorithms. © 2018 IEEE.
2018 International Conference on Artificial Intelligence and Data Processing, IDAP 2018 -- 28 September 2018 through 30 September 2018 -- Malatya -- 144523
Keywords: benchmarking function; constrained problems; Metaheuristic; optimization